Fatima’s Mimicry in Aliya Husain’s Neither This Nor That - Asiyah, Nur (UIN Syarif Hidayatullah Jakarta, 2022)
This study aims to reveal Fatima’s mimicry as the prominent figure in Aliya Husain’s Neither This Nor That. The presence of minorities often brings the assumption that they are foreign people, so they are treated discriminatively. Immigrants who live a new life in a country whose ideology, beliefs, and lifestyle of the original population are opposite to those of their home country will experience identity problems. Muslim women or Muslimah who are diaspora from India to America also share the same thing. They have to negotiate their identity, so they can live comfortably. The form of negotiation can be done by mimicry. This research is qualitative descriptive research. This research examines mimicry narratives from a diaspora novel, Neither This Nor That (2010). In addition, other sources such as books, journals, and the web are supporting sources. This paper uses Homi Bhabha's postcolonialism theory, especially mimicry, ambivalence, and hybrid. Ting Tomey's Identity Negotiation Theory is also used to strengthen the analysis. This study reveals that the characters imitate the majority's behavior subconsciously to maintain and save their identity. In doing so, they wait for the right time and momentum to negotiate their identity so that, in the end, a hybrid identity will emerge that accommodates the old and new identities.